2020
DOI: 10.1186/s13287-020-02043-5
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing of equine mesenchymal stromal cells from primary donor-matched tissue sources reveals functional heterogeneity in immune modulation and cell motility

Abstract: Background The efficacy of mesenchymal stromal cell (MSC) therapy is thought to depend on the intrinsic heterogeneity of MSC cultures isolated from different tissue sources as well as individual MSCs isolated from the same tissue source, neither of which is well understood. To study this, we used MSC cultures isolated from horses. The horse is recognized as a physiologically relevant large animal model appropriate for translational MSC studies. Moreover, due to its large size the horse allows f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 81 publications
5
35
0
Order By: Relevance
“…For MSCs from different sources, although their proliferation and differentiation abilities are similar, they may show different specific phenotypes and immunomodulatory properties, resulting in differences in efficacy. Harman et al ( 25 ) performed single-cell RNA sequencing (scRNA-seq) on primary equine MSCs that were collected from adipose tissue, bone marrow, and peripheral blood. They observed that transcriptional differences corresponded with phenotypic variance in cellular motility and the immune regulatory function ( 25 ).…”
Section: The Immunosuppressive Effect Of Mscs and Its Mechanismmentioning
confidence: 99%
“…For MSCs from different sources, although their proliferation and differentiation abilities are similar, they may show different specific phenotypes and immunomodulatory properties, resulting in differences in efficacy. Harman et al ( 25 ) performed single-cell RNA sequencing (scRNA-seq) on primary equine MSCs that were collected from adipose tissue, bone marrow, and peripheral blood. They observed that transcriptional differences corresponded with phenotypic variance in cellular motility and the immune regulatory function ( 25 ).…”
Section: The Immunosuppressive Effect Of Mscs and Its Mechanismmentioning
confidence: 99%
“…Additional studies from our group identified anti-microbial peptides in the horse PB-MSC secretome that inhibit the growth of contaminating bacteria commonly found in skin wounds, as well as cysteine proteases that destabilize bacterial biofilms in vitro ( Harman et al, 2017b ; Marx et al, 2020 ). Moreover, we confirmed that the chemokine C-X-C motif ligand 6 (CXCL6) secreted by horse PB-MSC acts as a chemoattractant for neutrophils in vitro ( Harman et al, 2020 ). Collectively, our research has identified specific factors secreted by PB-MSC that promote various aspects of skin wound healing, supporting the notion that the complete MSC secretome provides therapeutic benefits by targeting various aspects of specific disease processes.…”
Section: The Secretome Of Mesenchymal Stromal Cells (Mscs) From Vetermentioning
confidence: 56%
“…Single-cell RNA sequencing of mouse BM-derived MSCs revealed multiple profiles as well, some associated with distinct differentiation potential ( Freeman et al, 2015 ). Our group used single-cell transcriptomics to analyze donor-matched equine MSCs isolated from three different tissue sources and we found inter- and intra-source genetic heterogeneity that resulted in functional heterogeneity in immune function and cell motility ( Harman et al, 2020 ). The emerging technology of high-resolution precision proteomics is currently only being used to evaluate cancer cellular heterogeneity ( Waas and Kislinger, 2020 ), but will certainly be transferrable to MSCs, where this technique can provide additional insights into the heterogeneity of MSC populations to allow for the purification of MSC subpopulations with high secretory potential.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations